Business Letters for All. - Naterop, Bertha J., Weis, Erich and Haberfellner,E (Oxford Oxford University Press, 1996)
A practical guide to business correspondence for intermediate and advanced students of commercial English, and anyone who needs to improve his command of English correspondence in the course his job. This book includes model letters, in American as well as British English, and phrases on typical business matters in realistic international contexts. There are exercises at the end followed by a comprehensive reference vocabulary of business words with examples and compound words. An answer key to the exercises is also provided.
Keywords: Business English